2012
DOI: 10.1371/journal.pone.0034647
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid B Prevents Bone Loss in Prednisone-Treated Rats through Stimulation of Osteogenesis and Bone Marrow Angiogenesis

Abstract: Glucocorticoid (GC) induced osteoporosis (GIO) is caused by the long-term use of GC for treatment of autoimmune and inflammatory diseases. The GC related disruption of bone marrow microcirculation and increased adipogenesis contribute to GIO development. However, neither currently available anti-osteoporosis agent is completely addressed to microcirculation and bone marrow adipogenesis. Salvianolic acid B (Sal B) is a polyphenolic compound from a Chinese herbal medicine, Salvia miltiorrhiza Bunge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
120
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(137 citation statements)
references
References 44 publications
13
120
3
1
Order By: Relevance
“…Excessive Dex can evoke osteoporosis by depressing osteoblastic bone formation in humans and higher vertebrates. Excess GC also inhibits osteoblast differentiation and bone nodule formation in bone marrow stroma stem cells [1] , consistent with our previous studies [16] . Furthermore, previous reports indicate that GC induces the inhibition of osteogenesis in zebrafish larvae 21 , consistent with our present results.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Excessive Dex can evoke osteoporosis by depressing osteoblastic bone formation in humans and higher vertebrates. Excess GC also inhibits osteoblast differentiation and bone nodule formation in bone marrow stroma stem cells [1] , consistent with our previous studies [16] . Furthermore, previous reports indicate that GC induces the inhibition of osteogenesis in zebrafish larvae 21 , consistent with our present results.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous study [16,18] showed that Sal B in vitro promoted bone marrow stromal cell differentiation into osteoblasts, increased osteoblast activity and decreased GC associated adipogenic differentiation. Moreover, an aqueous extract of Radix Salviae miltiorrhizae, of which the main ingredient is Sal B, prevented GC-induced bone loss [16] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations